Molecular detection of IBV from backyard chickens in Diyala province - Manswr, Basim M.; Al-Khalidi, Akram Ahmed Hassan; Ali, Aws El-Muntaser H. (Diyala Journal for Veterinary Sciences, 2023)
Globally, chickens are infected with the economically significant viral disease known as infectious bronchitis virus (IBV). Finding endemic IBV strains helps reduce production losses and improves control of these illnesses. Nine backyard flocks in Diyala were used to collect samples from 90 birds using Oropharyngeal and cloacal swabs. Using part-S1 gene primers for IBV, RT-PCR was performed on swabs from each sample. Nine samples of chicken were positive for IBV, with an incidence rate of 9.9% overall and 1.1% in each investigated location. These positive samples were genotyped, and they shared similarities with M41 and 1494/06, similar to IBV. Identified viruses, especially mutant IBV strains, may still be a threat to backyard and commercial chickens even though no disease was evident at the time of sampling in poultry in Diyala province.